Implementasi Kebijakan Pembinaan Bahasa Daerah di Kabupaten Jember, Situbondo dan Banyuwangi - Budi Suyanto (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2017)
This study discusses about the relation between students’ bilingualism (particularly second language learners) acquired through studying at school and student’s capability in inter-ethnic social interaction. It is assumed that local language teaching at school provides students capability of bilingualism. Students’ bilingualism plays important role in their multicultural perspective endorsing them to have tolerance and solidarity to different ethics and culture, all of which are the factors to build harmony in plural society. Observed subjects are secondary school students with plural cultural backgroundsin Jember, Situbondo, and Banyuwangi. As a matter of fact, people in those three regencies have plural cultural background, however, the teaching of local language is different. This research is conducted with analytic-quantitative paradigm. Data analysis is conducted in two ways: (a) qualifying andgeneralizing dataand (b) qualifying and relating data with their social context. The result shows that (1) learning local language at 6 secondary schools in the three regencies has impact ondifferent achievements concerning students’ bilingualism; (2) there is a correlation between students’ bilingualismand their capability of having interaction with different ethnic; (3) there is a correlation between students’ language performance and their solidarity, tolerance and integrity with people of different ethnics. (4) the consequence of teaching only majorities’ local language is that students’ of major ethnic merely have competence of their own local language, and thus have less capability of bilingualism concerning local language of different ethnic. Students’ linguistic repetoir are not improved. On the other hand, students from minor ethnic do not get competence of their own local language but get other ethnic’s local language instead. Students of minor ethnic have advantage in that they are able to take part in their social role using their competence of major ethnic’s local language. However, it also has negative impact in that they have limited competence in their own local language and culture, and gradually lose their own identity as they become dominated by major ethnic. Keywords: language teaching, multiculturalism, bilingualism, intercultural communication